(untitled) (Research, Society and Development, 2022)
With the advancement of technologies there has also been a growth in the use of social media, making these the main forms of communication between users, there are several platforms that can be used in different ways for different purposes. Dentistry as well as other areas have used this means of communication as a form of teaching, marketing, information dissemination platforms, among others. In the dental environment, there has been a concern about the types of content that are being disseminated, since these may not have a scientific basis, they may be disseminating inappropriate images, making undue exposure of patients, making use of images only for the purpose of capitation. of patients. In this sense, when making use of these social media, professionals must pay attention to the type of content that will be shared, they must also pay attention to the norms present in the dental ethics code and that are currently in force, so that in this way, they do not commit any type of inflation. This work aims to analyze the use of social media in dentistry. Evidencing impacts and possibilities that the use of these social media has provided to the dental area. The literary search took place on the platforms: Google Scholar and Medical Literature Analysis and Retrieval System Online (Pubmed) and selected according to the theme. After analyzing the works, it is concluded that social media, depending on how they will be used, can impact both positively and negatively on the lives of professionals, students and patients.